2021
DOI: 10.1016/j.xcrm.2021.100474
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic effects of direct AMP kinase activation in humans with insulin resistance and non-alcoholic fatty liver disease: A phase 1b study

Abstract: Summary AMPK is an energy sensor modulating metabolism, inflammation, and a target for metabolic disorders. Metabolic dysfunction results in lower AMPK activity. PXL770 is a direct AMPK activator, inhibiting de novo lipogenesis (DNL) and producing efficacy in preclinical models. We aimed to assess pharmacokinetics, safety, and pharmacodynamics of PXL770 in humans with metabolic syndrome-associated fatty liver disease. In a randomized, double-blind four-week trial, 12 overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…Importantly, we sought to establish if PXL770 treatment could reduce VLCFA in key target tissues in vivo. Of note, a single dose study showed that plasma PK parameters measured in the Abcd1 null mice were also within, or modestly below, exposure levels previously reported in a Phase 1B study where patients with non-alcoholic fatty liver were receiving 500 mg QD PXL770 (Fouqueray et al, 2021). Although PXL770 in vivo treatment did not fully normalize elevations in VLCFA in brain or spinal cord, significant reductions were noted.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Importantly, we sought to establish if PXL770 treatment could reduce VLCFA in key target tissues in vivo. Of note, a single dose study showed that plasma PK parameters measured in the Abcd1 null mice were also within, or modestly below, exposure levels previously reported in a Phase 1B study where patients with non-alcoholic fatty liver were receiving 500 mg QD PXL770 (Fouqueray et al, 2021). Although PXL770 in vivo treatment did not fully normalize elevations in VLCFA in brain or spinal cord, significant reductions were noted.…”
Section: Discussionmentioning
confidence: 62%
“…A single potential additional target was identified, with weak inhibition of CCK1 during a receptor binding assay (Gluais-Dagorn et al, 2021). Substantial preclinical and clinical efficacy was demonstrated on multiple metabolic disease related features in animals and humans with non-alcoholic fatty liver disease (NAFLD), Type 2 diabetes, obesity and insulin resistance (Cusi et al, 2021;Fouqueray et al, 2021;Gluais-Dagorn et al, 2021). Importantly, PXL770 is the first direct AMPK activator to have progressed to clinical trials for any disease.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, indiscriminate AMPK activation, either by pan-AMPK activators or naturally occurring mutations in the PRKAG2 gene encoding the AMPKγ2 subunit, tends to cause cardiac disorders 37,[88][89][90] . However, two other AMPK agonists, salsalate (a pro-drug of salicylic acid) and PXL770, that show the efficacy of lowering blood glucose and alleviating NAFLD 48,91,92 have been under clinical trials and have shown favourable safety profiles [93][94][95][96] . Interestingly, both of the two agonists are AMPKβ1 specific, leaving the AMPKβ2-comprised AMPK complex inactivated 48,92 .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled trial reported that treatment using PXL770 for 12 weeks decreased DNL percentage and improved glucose metabolism. Lipid profiles concerning triglycerides and very-low-density lipoprotein (VLDL) decreased in the PXL770 group compared to the placebo group (65). Furthermore, AMPK activation, direct or indirect, has a beneficial effect by reducing steatosis in patients with NAFLD.…”
Section: Nafld For 6 Monthsmentioning
confidence: 98%
“…Another study with a direct AMPK activator, PXL770, supports this statement. The mechanisms of action of metformin and PXL770 as activators of AMPK are summarized in Table II (58)(59)(60)(61)(62)(63)(64)(65)(66)(67). A randomized, double-blind, placebo-controlled trial reported that treatment using PXL770 for 12 weeks decreased DNL percentage and improved glucose metabolism.…”
Section: Nafld For 6 Monthsmentioning
confidence: 99%